Perlindungan Hukum Terhadap Konsumen Dalam Transaksi Jual Beli Rumah Melalui Developer Di Kabupaten Badung - I Komang Bagus Shadewa; Made Emy Andayani Citra (Jurnal Hukum Mahasiswa, 2026)
The increasing housing development activity in Badung Regency has given rise to various issues related to legal protection for consumers. Therefore, there is an urgent need to raise legal awareness and strengthen consumer protection in the property sector in Badung Regency. The research method used is an empirical research method with a factual and legislative approach. Data collection techniques included interviews, direct observation, document studies, and literature. Based on the research results, it is clear that consumer legal protection in home sales transactions through developers in Badung Regency is affected by the property owners' frequent breach of contract regarding property delivery due to delays in construction, citing reasons such as construction workers leaving work, permits, and unfinished construction, which clearly harms consumers. Legislation regulates consumer protection, but it has not been implemented effectively by both businesses and consumers. Obstacles to consumer legal protection in home sales transactions through developers in Badung Regency are influenced by various factors, including those related to the legal structure, legal substance, legal culture, and bureaucratic apparatus. Broadly speaking, the obstacles or barriers faced in the implementation of the Consumer Protection Law (UUPK) are still facing various challenges